2011
DOI: 10.1503/cjs.007810
|View full text |Cite
|
Sign up to set email alerts
|

Factors that determine whether a patient receives completion axillary lymph node dissection after a positive sentinel lymph node biopsy in breast cancer in British Columbia

Abstract: Factors that determine whether a patient receives completion axillary lymph node dissection after a positive sentinel lymph node biopsy for breast cancer in British Columbia Background: Completion axillary lymph node dissection (CALND) is recommended in the setting of positive sentinel lymph node biopsy (SLNB) but is associated with a higher rate of postoperative complications. In this study, the characteristics and outcomes of patients who did and did not have CALND are compared. Methods:We identified all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
1
3
0
Order By: Relevance
“…It is also supported by another study by Swanson and Kennecke which shows a higher percentage of positive SLNs to be predictive of higher likelihood of axillary lymph node (ALN) involvement as well as decreased survival [8]. In this study, the presence of extracapsular invasion in the positive SLN the more the number of positive LN that has been found in axillary evacuation as 7 on the status of the axilla itself [8].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is also supported by another study by Swanson and Kennecke which shows a higher percentage of positive SLNs to be predictive of higher likelihood of axillary lymph node (ALN) involvement as well as decreased survival [8]. In this study, the presence of extracapsular invasion in the positive SLN the more the number of positive LN that has been found in axillary evacuation as 7 on the status of the axilla itself [8].…”
Section: Discussionsupporting
confidence: 53%
“…It is also supported by another study by Swanson and Kennecke which shows a higher percentage of positive SLNs to be predictive of higher likelihood of axillary lymph node (ALN) involvement as well as decreased survival [8]. In this study, the presence of extracapsular invasion in the positive SLN the more the number of positive LN that has been found in axillary evacuation as 7 on the status of the axilla itself [8]. Multivariate analysis also showed that primary tumor size also significantly influenced the risk of non-SLN involvement, the risk was 0% in patients with pT1a, b tumors, 17% in those with pT1c tumors, and 67% in those with tumors measuring more than 20 mm.…”
Section: Discussionmentioning
confidence: 55%
“…In retrospective studies, older age, severe comorbidities, smaller tumor size, low grade, and hormone receptor positivity were reported as the most frequent reasons for avoiding axillary dissection [15,17] . Besides, higher number of removed sentinel lymph nodes, lower percentage of positive sentinel lymph nodes and pathologic N stage support the decision on only SLNB [18] . In addition, surgeons feel reluctant to perform axillary dissection when metastases in the sentinel lymph nodes were identified postoperatively.…”
Section: Axillary Management In Case Of Sentinel Lymph Node Positivitymentioning
confidence: 95%
“…In addition, surgeons feel reluctant to perform axillary dissection when metastases in the sentinel lymph nodes were identified postoperatively. Low axillary recurrence rates reported in retrospective studies encouraged the surgeons not to perform completion axillary dissection [18][19][20][21] . Presence of metastases in the remaining axilla in only 40%-60% of patients led to the development of nomograms to predict the patients with further metastases in the axilla [12] .…”
Section: Axillary Management In Case Of Sentinel Lymph Node Positivitymentioning
confidence: 99%